Associations between Maternal Behaviors at 1 Year and Child Language at 2 Years in a Cohort of Women Experiencing Adversity. (1st August 2017) - Smith, Jodie; Levickis, Penny; Eadie, Tricia; Bretherton, Lesley; Conway, Laura; Goldfeld, Sharon
Abstract : Variations in parenting have been suggested as contributing to a higher prevalence of language difficulties in children experiencing economic, environmental, and social adversity. Within these cohorts, the contribution of responsive and intrusive parenting to child language has been investigated; s pecific responsive and intrusive behaviors encapsulated within these parenting styles have yet to be fully examined. Additionally, the role of the mother–child dynamic in moderating mother–child associations has also not been explored. This study aimed to augment current research by identifying specific responsive and intrusive maternal behaviors associated with child language in a cohort experiencing adversity, as well as exploring the role of the fluency and connectedness of mother–child conversation in moderating associations ( n  =   249). Specific behaviors and the fluency and connectedness of the mother–child interaction were coded from free‐play videos at child age 12 months. Child language measures were derived from transcripts of free play at 24 months. Linear regression models were used to examine maternal–child associations. The moderating role of fluency and connectedness was then explored. Maternal imitations were positively associated with the child's total words; successful redirectives were negatively associated with the child's mean length of turn. Both associations were moderated by the fluency and connectedness of the interaction.